Bertasawuf Di Era Modern: Tasawuf Sebagai Psikoterapi - Endang Sri Rahayu (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2021)
“And we reveal of the Qur´an that which is a healing and a mercy for believers” (Q.S. Al-Isra 17:82). In this verse, Allah affirm that in Qur’an there’s a cure or medicine. The mental issue is one of the many issues concerning human health. The clinical approach to cure mental issue without the help medicinal drugs are what came to be known as psychotherapy. Islam, as the embodiment of the Qur’anic values, as the previous verse has affirm as well, provide solutions. Sufism, which takes Qur’an as it basis for it’s mysticism and spiritual practices, is the representation of Qur’anic and Islamic way to provide psychotherapy.